Dukungan sosial teman sebaya dengan tingkat quarter life crisis pada individu dewasa awal - Hariyanto, Dandy Putra; Rina, Amherstia Pasca; Sukiatni, Dwi Sarwindah (JIWA: Jurnal Psikologi Indonesia, 2024)
Abstract This research aims to determine the relationship between peer social support and the level of quarter life crisis in early adult individuals. The subjects of this research were vulnerable individuals aged 19-29 years in the city of Surabaya with a total of 100 respondents. Based on analytical calculations using Spearman Rho, a correlation score of 0.225 was obtained with a significance level of 0.000 (p<0.05), meaning that there was no negative relationship between social support and the quarter life crisis. The result is that the higher the social support an individual has, it has no effect on the level of quarter life crisis experienced by that individual. Keywords: social support, Quarter life crisis, adult individuals Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial teman sebaya dengan tingkat quarter life crisis pada individu dewasa awal. Subjek penelitian ini adalah individu di rentan usia 19-29 tahun yang ada di kota Surabaya dengan jumlah responden 100 orang. Berdasarkan perhitungan analisis menggunakan Spearman Rho diperoleh skor korelasi Sebesar 0.225 dengan taraf signifikansi sebesar 0.000 (p<0.05) artinya tidak terdapat hubungan negatif antara dukungan sosial dengan quarter life crisis. Hasilnya semakin tinggi dukungan sosial yang dimiliki individu tidak berpengaruh terhadap tingkat quarter life crisis yang dialami oleh individu tersebut. Kata Kunci: Dukungan Sosial, Quarter life crisis, Remaja Awal